The contribution of 3D models to the study of stone monuments in the Maya area - Philippe Nondédéo; Julien Hiquet; Rémi Mereuze; Hemmauthé Goudiaby; Nikolai Grube (IdeAs)
The Maya area is known for its numerous monuments sculpted in limestone, which suffered severe erosion over time. The Mayas used soft limestone, which is sensitive to weathering, to carve iconographic motives and inscriptions on stelae, altars and panels. A systematic program of documentation was developed for monuments considered plain—without reliefs visible to the naked eye. Thanks to photogrammetry and various treatments generated from photographic recordings, a series of new data has been revealed, enriching our knowledge of the political history of the Maya cities. This case study is centered on a selection of monuments from the urban Maya center of Naachtun (Classic period, 150-950 CE) and contains useful archaeological, epigraphic and historical data. Our objective is also methodological and aims to report on treatments generated from photographic recording. Diverse and rich, these treatments can be applied on weathered monuments to enhance their relief.